On the exposure of hands to vibration in road cycling: an assessment of the effect of gloves and handlebar tape - Drouet, J.-M.; Covill, D.; Duarte, W. (Proceedings, 2018)
The objective of this work was to assess the effectiveness of cycling gloves and handlebar tape in reducing the vibration transmitted to the cyclist`s hands in the classic "hoods" position for shock-type excitation at the front wheel on a bicycle treadmill. Three pairs of conditions were tested on a single participant: (1) With gloves vs. no gloves, no bar tape; (2) With bar tape vs. no bar tape, no gloves; (3) With gloves and bar tape vs. no gloves and no bar tape. We have shown that a rider can expect a small but significant drop in the level of transmitted power and energy through the handlebars when wearing a standard pair of road cycling gloves. If bar tape is used however (both with and without gloves), there is a significantly larger drop in the level of transmitted power and energy through the handlebars.